Reflection On Strengthening Hindu Law in The Era of Globalization - Budiana, I Nyoman; Mahadewi, Kadek Julia (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The development of the times has made several shifts that occur in life, one of the concerns that arise about local wisdom that occurs in society regarding the flow of globalization and the dependence of culture in society. The existence of Hindu law in a dynamically applicable society. The problem raised in the writing of this journal is how does Hindu law exist in the era of globalization? The research method in this journal uses a normative method, the approach uses a legislative approach, the legal sources are primary sources and secondary sources, the technique of collecting legal materials, the study of documents and the analysis technique uses descriptive. Hindu law and customary law in the national legal system have not yet been compiled into positive law (ius constitutum), because they have not been established as formal laws and regulations in accordance with Law No. 12 of 2011 concerning the Establishment of Laws and Regulations.